Analisis Strategi Pemasaran Game Genshin Impact Pada Pasar Game Global Di Indonesia - Po, Michael; Mega, Selfia Alke (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The rapid development of the global gaming industry has prompted companies such as Hoyoverse to formulate effective strategies to enhance their competitiveness. This article analyzes Hoyoverse's corporate strategy in enhancing competitiveness in the global gaming market, focusing on the role of the game Genshin Impact. The review involves the background of the gaming industry, company profile, and key elements of Genshin Impact. The aim is to identify key factors that influence Hoyoverse's competitiveness and investigate the impact of Genshin Impact on the company's position in the global market. The research methodology involves literature analysis, field research, and evaluation of the company's financial data. The results are expected to provide in-depth insights into Hoyoverse's strategy and Genshin Impact's contribution to enhancing its competitiveness in the global gaming market.